Resin-based sodium ion battery hard carbon material and preparation method thereof

By mixing the resin with cellulose-based derivatives and performing specific treatment, a hard carbon material with a good specific surface area is prepared, which solves the problem of poor electrochemical performance of existing sodium ion battery hard carbon materials, and achieves higher Coulomb efficiency, cycle stability and rate performance.

CN119612494APending Publication Date: 2025-03-14HUNAN FENGRI ELECTRIC GROUP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411913253.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing hard carbon materials of sodium ion batteries have low conductivity, small specific surface area, defects and many micropores, poor initial Coulomb efficiency, poor cycle stability and rate performance.

Method used

The resin and cellulose-based derivative are mixed with heat treatment to form a crosslinked precursor, and then pretreatment, pickling and high-temperature carbonization are performed under an inert atmosphere to prepare a hard carbon material with a good specific surface area.

Benefits of technology

The first-time Coulomb efficiency, cycle performance and rate performance of sodium ion batteries are improved, and the electrochemical performance of hard carbon materials is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612494A_ABST
    Figure CN119612494A_ABST
Patent Text Reader

Abstract

The invention discloses a resin-based sodium-ion battery hard carbon material and a preparation method thereof, and relates to the technical field of sodium-ion battery material preparation. The preparation method comprises the following steps: carrying out cross-linking reaction on a mixture of resin and a cellulose-based derivative to obtain a cross-linked precursor, and then carrying out pretreatment and high-temperature carbonization on the precursor to obtain the resin-based sodium-ion battery hard carbon material. The adopted resin and cellulose derivative have the advantages of low cost and wide source, have rich functional groups, and can be used as cross-linking agents to improve the cross-linking degree of the precursor, reduce the specific surface area of the hard carbon material and improve the first coulombic efficiency; carbonate generated in the pretreatment process of the cellulose derivative can be used as a salt template to regulate and control the internal pore structure of hard carbon. The rich pore structure is beneficial to permeation of electrolyte, the diffusion path of sodium ions can be shortened, and active sites of hard carbon are fully utilized, so that the cycling stability and the rate capability of the sodium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery material preparation, and specifically relates to a resin-based sodium ion battery hard carbon material and a preparation method thereof. Background Art

[0002] The global economy is growing rapidly, and the demand for energy is becoming increasingly urgent. Although fossil energy is dominant today, its scarcity and environmental problems are becoming increasingly prominent. Renewable energy such as solar energy, tidal energy and wind energy are considered to be the main development direction in the future, which can promote low-carbon transformation and reduce greenhouse gas emissions. However, finding suitable energy storage devices still faces challenges and requires continuous innovation. Sodium-ion batteries have attracted much attention because of their working principle similar to that of lithium-ion batteries, low cost and abundant resources. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: First, the natural reserves of sodium are more abundant and more evenly distributed than lithium; Second, in sodium-ion batteries, aluminum foil can be used as a current collector on both the anode and cathode sides, and its cost is lower than that of lithium-ion batteries. Therefore, sodium-ion batteries are generally regarded as a low-cost alternative to lithium-ion batteries. Although the research on electrode materials of lithium-ion batteries has provided valuable experience for sodium-ion batteries, due to the larger radius of sodium ions and lithium ions, the reduction potential is 300 mV, which is also higher than that of lithium ions. These differences lead to large volume changes during the cycle, which can easily cause material pulverization, increased diffusion barriers, slow reaction kinetics and other problems. Therefore, finding suitable electrode materials remains the main focus of current sodium-ion battery research.

[0003] Hard carbon is considered to be the most promising negative electrode material for sodium ion batteries due to its large interlayer spacing, more nanopores, low cost and stable structure. However, the disordered structure of hard carbon leads to its low conductivity, and the direct carbonization precursor releases a large amount of small gas molecules to form a carbon skeleton with a large specific surface area. There are a large number of defects and micropores on the surface of the carbon anode, which may induce the decomposition of the electrolyte and lead to the formation of a thick solid electrolyte layer. This phenomenon leads to poor initial coulombic efficiency. In addition, the low specific surface area and limited defect sites are not conducive to the improvement of cycle stability and rate performance. Summary of the invention

[0004] The object of the present invention is to provide a resin-based sodium ion battery hard carbon material and a preparation method thereof, wherein the hard carbon material has a good specific surface area, and the prepared battery has good first coulombic efficiency, cycle performance and rate performance.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) heating a mixture of a resin and a cellulose-based derivative under an air atmosphere to obtain a cross-linked precursor; (2) pretreating the cross-linking precursor under an inert atmosphere; (3) acid-washing the pretreated powder and filtering and drying it to remove salt from the powder; (4) The acid-washed powder is carbonized at high temperature under an inert atmosphere to obtain hard carbon.

[0006] It should be noted that the resin and the cellulose-based derivative in step (1) are mixed by manual grinding for 10-30 minutes.

[0007] It should be noted that the mass ratio of the resin to the cellulose-based derivative in step (1) is 1:0.5-2.5.

[0008] It should be noted that the cellulose-based derivative in step (1) is at least one selected from sodium carboxymethyl cellulose, potassium carboxymethyl cellulose or calcium carboxymethyl cellulose.

[0009] It should be noted that the heat treatment temperature in step (1) is 80-120°C and the reaction time is 2-6h.

[0010] It should be noted that the inert atmosphere in step (2) is at least one of nitrogen or argon.

[0011] It should be noted that the pretreatment temperature in step (2) is 200-600°C, the holding time is 2-4h, and the heating rate is 1-5°C / min.

[0012] It should be noted that the acid used for pickling in step (3) is one of dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid, and the pickling time is 2-8 hours.

[0013] It should be noted that the drying method in step (3) is forced air drying, the drying temperature is 60-100° C., and the drying time is 8-20 h.

[0014] It should be noted that the inert atmosphere in step (4) is at least one of nitrogen or argon.

[0015] It should be noted that the carbonization temperature in step (4) is 1100-1500°C, the holding time is 1-3h, and the heating rate is 1-8°C / min.

[0016] Beneficial effects of the present invention: (1) The resin and cellulose derivatives used in the present invention have the advantages of low cost and wide sources, and both have rich functional groups, which can be used as cross-linking agents to increase the cross-linking degree of the precursor, reduce the specific surface area of ​​the hard carbon material, and improve the first coulombic efficiency; (2) The preparation method of the present invention is simple, and the carbonate produced during the pretreatment of the cellulose derivative can be used as a salt template to regulate the internal pore structure of the hard carbon. This rich pore structure is conducive to the penetration of the electrolyte, shortens the diffusion path of sodium ions, and fully utilizes the active sites of the hard carbon, thereby improving the cycle stability and rate performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the hard carbon material prepared in Example 5 of the present invention; Figure 2 This is a schematic diagram of XRD of the hard carbon material prepared in Example 5 of the present invention; Figure 3 This is a charge and discharge curve diagram of the sodium ion battery prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention is further described in detail below in conjunction with specific implementation methods: Example 1

[0019] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and sodium carboxymethyl cellulose were ground and mixed at a mass ratio of 1:0.5 for 20 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 80°C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 200 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove potassium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1300 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon. Example 2

[0020] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and sodium carboxymethyl cellulose were ground and mixed at a mass ratio of 1:1.5 for 20 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 100°C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 400 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove potassium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1300 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon. Example 3

[0021] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and sodium carboxymethyl cellulose were ground and mixed at a mass ratio of 1:2.5 for 20 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 120°C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 600 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove potassium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1300 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon. Example 4

[0022] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and sodium carboxymethyl cellulose were ground and mixed at a mass ratio of 1:1 for 10 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 100°C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 300 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove sodium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1100 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon. Example 5

[0023] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and potassium carboxymethyl cellulose were ground and mixed at a mass ratio of 1:1 for 20 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 100 °C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 300 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove potassium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1300 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon. Example 6

[0024] A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) In an air atmosphere, the resin and carboxymethyl cellulose calcium were ground and mixed at a mass ratio of 1:1 for 30 minutes, and then the mixture was transferred to a homogeneous reactor and reacted at 100°C for 5 hours to obtain a cross-linked precursor; (2) In a nitrogen atmosphere, the cross-linked precursor was heated to 300 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h; (3) adding the pretreated powder to dilute hydrochloric acid, stirring and acid washing for 4 hours, and filtering and drying to remove sodium carbonate in the powder; (4) Under an argon atmosphere, the acid-washed powder is heated to 1500 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon.

[0025] Comparative Example 1 A resin-based sodium ion battery hard carbon material and a preparation method thereof, comprising: (1) Under air atmosphere, transfer the resin into a homogeneous reactor and keep it at 100 °C for 5 h; (1) In a nitrogen atmosphere, the precursor was heated to 300 °C at a heating rate of 2 °C / min and kept at this temperature for 4 h. (2) Under an argon atmosphere, the powder was heated to 1300 °C at a heating rate of 5 °C / min and kept at this temperature for 2 h to obtain hard carbon.

[0026] Test Example 1 The electrochemical properties of hard carbon materials were tested using a half-cell test method. The constant current charge and discharge (GCD) test was carried out on a Xinwei test channel with a cut-off voltage range of 0.01-2.5V and a cycle test current density of 0.1C (30 mA g -1 ) and 1C(300 mA g -1 ), all electrochemical experiments were carried out at room temperature.

[0027] Table 1 Test results of electrochemical properties of materials project First coulombic efficiency (%) 0.1C reversible specific capacity (mAh / g) 1C reversible specific capacity (mAh / g) Example 1 88.1 314 281 Example 2 86.4 322 285 Example 3 86.2 313 270 Example 4 87.7 334 289 Example 5 89.4 349 298 Example 6 85.1 322 282 Comparative Example 1 82.6 267 224 From the test results, the resin-based sodium ion battery hard carbon material produced by the method of the present invention has better first coulombic efficiency and reversible specific capacity than the control example.

[0028] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Any modification, replacement or modification made by any technician familiar with the profession using the above-disclosed technical contents without departing from the scope of the technical solution of the present application are equivalent to equivalent implementation cases and are included in the protection scope of the present invention.

Claims

1. A method for preparing a resin-based sodium ion battery hard carbon material, comprising: (1) grinding a mixture of a resin and a cellulose-based derivative for 10-30 minutes under an air atmosphere, followed by a cross-linking reaction to obtain a cross-linked precursor, wherein the cellulose-based derivative is selected from at least one of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, or calcium carboxymethyl cellulose; (2) pretreating the cross-linking precursor under an inert atmosphere, wherein the inert atmosphere is at least one of nitrogen or argon; (3) acid-washing the pretreated powder and filtering and drying it to remove salt from the powder; (4) Carbonizing the acid-washed powder at high temperature under an inert atmosphere to obtain hard carbon, wherein the inert atmosphere is at least one of nitrogen and argon.

2. The method for preparing a resin-based sodium ion battery hard carbon material according to claim 1, characterized in that: In step (1), the mass ratio of the resin to the cellulose-based derivative is 1:0.5-2.

5.

3. The resin-based sodium ion battery hard carbon material and preparation method thereof according to claim 1, characterized in that: The temperature of the cross-linking reaction in step (1) is 80-120° C., and the reaction time is 2-6 hours.

4. The method for preparing a resin-based sodium ion battery hard carbon material according to claim 1, characterized in that: The pretreatment temperature in step (2) is 200-600°C, the holding time is 2-4h, and the heating rate is 1-5°C / min.

5. The method for preparing a resin-based sodium ion battery hard carbon material according to claim 1, characterized in that: The acid used for pickling in step (3) is one of dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid, and the pickling time is 2-8 hours.

6. The method for preparing a resin-based sodium ion battery hard carbon material according to claim 1, characterized in that: The drying method in step (3) is forced air drying, the drying temperature is 60-100° C., and the drying time is 8-20 hours.

7. The method for preparing a resin-based sodium ion battery hard carbon material according to claim 1, characterized in that: The carbonization temperature in step (4) is 1100-1500°C, the holding time is 1-3h, and the heating rate is 1-8°C / min.

8. A resin-based sodium ion battery hard carbon material, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 7.

9. An application of a resin-based sodium ion battery hard carbon material, characterized in that: The resin-based sodium ion battery hard carbon material according to claim 8 is used in the field of sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method and modification method of hard carbon negative electrode material for lithium ion power batteries

    CN106981629A

  • Negative electrode material and preparation method and application thereof

    CN115602812A

  • Preparation method and application of hard carbon negative electrode material

    CN117957189A

  • Negative electrode material, preparation method thereof and battery

    CN118270766A

  • Hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN118754100A